2006
DOI: 10.1136/jech.2005.044255
|View full text |Cite
|
Sign up to set email alerts
|

Influence of socioeconomic status on clinical outcomes and quality of life after percutaneous coronary intervention

Abstract: Objectives: To determine whether socioeconomic status (SES) influences clinical outcomes and quality of life after percutaneous coronary intervention (PCI). Design: Prospective observational study. Setting: Two interventional cardiac centres. Participants: 1346 consecutive patients undergoing PCI over a 12-month period. Outcomes: Self reported health-related quality of life (HRQoL; EuroQol-5 Dimensions (EQ-5D); EuroQol Visual Analogue Scale (EQ-VAS)), repeat angiography, revascularisation, hospital admission, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 21 publications
(9 reference statements)
5
45
2
1
Order By: Relevance
“…Next, associations between SES, cognitive-emotional factors, and health status appraisals one year following MI were examined. Consistent with other investigators, results showed low SES was associated with poor health status appraisals (e.g., Barbareschi et al, 2009;Denvir et al, 2006;Peters-Klimm et al, 2010). Of most relevance to the current study, results mostly supported the RCM when predicting psychological health status appraisals, particularly for the SF-12 MCS.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Next, associations between SES, cognitive-emotional factors, and health status appraisals one year following MI were examined. Consistent with other investigators, results showed low SES was associated with poor health status appraisals (e.g., Barbareschi et al, 2009;Denvir et al, 2006;Peters-Klimm et al, 2010). Of most relevance to the current study, results mostly supported the RCM when predicting psychological health status appraisals, particularly for the SF-12 MCS.…”
Section: Discussionsupporting
confidence: 90%
“…Quality of life is conceptualized as a patient's general sense of his/her health and well-being, and is generally best assessed through direct patient appraisals (Gyatt et al, 1993). Patients from low SES backgrounds who were treated with percutaneous coronary intervention had lower health-related quality of life during hospitalization and 12 months later than high SES patients (Denvir et al, 2006). A prospective study of older patients with CVD also showed differences in quality of life by SES before disease onset, and at 6 and 12 months post-diagnosis (Barbareschi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Denvir et al found no significant association between the individual's SES and cardiovascular outcomes [13]. This study may have been underpowered and was conducted before the introduction of drug eluting stents (DES), the utilization of which might be different among patients of different SES [14,15].…”
Section: Introductionmentioning
confidence: 98%
“…However, post-PCI QOL does not necessarily improve relative to pre-PCI in all patients. Factors affecting QOL among patients after elective PCI include smoking, weight gain, depression, unemployment and lack of family help [7][8][9][10][11][12][13][14][15]. Among these factors, smoking and weight gain are closely associated with lifestyle.…”
Section: Introductionmentioning
confidence: 99%